Student policies in teacher training: Pedagogical problems and debates in South American perspective - Birgin, Alejandra; Vassiliades, Alejandro (Education Policy Analysis Archives, 2018)
Within the framework of the process of enrollment expansion in teacher training (in the context of the expansion of the higher education level), some Latin American countries have developed specific policies for the student population of teacher training institutions. In this article we analyze how these policies bring new questions to the field of teacher training, linked to the ways in which “new” students are questioned and their effects on the construction of teaching positions. For this, we address a series of speeches from international organizations (with marked influence in the region), which coincide in describing future teachers as deficit subjects. At the same time, we go through a set of student policies that assumed diverse orientations regarding the right to education of these populations and regarding the right of their future students. We understand that these policies and discourses have an effect on the configuration of teaching positions with respect to educational inclusion.